PENGARUH KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN PADA PDAM KOTA MADIUN - Anum Reknowati Ningsih (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This study aims to determine the leadership and employee motivation on the taps Madiun and to determine whether there is influence on employee motivation leadership at Madiun taps. Data collection using questionnaires, documentation, and observation. The analytical tool used in this study is simple linear regression analysis correlation test load, f test and t test using SPSS for windows 16.0. The results showed that the leadership have influence at the same time a positive relationship to employee motivation at PDAM Madiun. This means that the value of fhit ≥ ftable (49.921 ≥ 3.37 or Sighit ≤ Sigtable (0,000 ≤ 0.05), or it can be concluded reject H0, meaning no overall effect between leadership on employee motivation in PDAM Madiun. In addition, reliability test results obtained from the value of Cronbach's Alpha 0.859 and 0.944> 0.70. This means that the data collected is reliable (trustworthy).